Quantitative comparisons of lung structure of adult domestic fowl and red jungle fowl, with reference to broiler ascites - Vidyadaran, M.K.; King, A.S.; Kassim, H. (Taylor and Francis Group, 1990)
A stereological comparison has been made of the structure of the lungs of the adult female domestic fowl and its wild progenitor the Red Jungle Fowl. The volume of the lung per unit body weight of the domestic bird is between 20 and 33% smaller than that of the wild bird. The domestic fowl has partly compensated for this by increasing the surface area for gas exchange per unit volume of exchange tissue. However, the blood-gas tissue barrier is about 28% thicker in the domestic fowl than in the Red Jungle Fowl, and this has led to a 25% lower anatomical diffusing capacity for oxygen of the blood-gas tissue barrier per unit body weight in the domestic fowl. These structural characteristics may make the modern domestic fowl vulnerable to stress factors such as altitude, cold, heat or air pollution by predisposing to hypoxaemia and perhaps thence to ascites.